(untitled) (Journal of Economic Research & Business Administration, 2016)
The usefulness of labor is an indicator of the quality of work. It reflects: how the product of labor is demanded by society as a use value and cost. Will the manufacturer (owner of capital) earn the expected revenues and earnings. Will the labor harm environmental and social damage. Only under these conditions, the labor will be evaluated as a real product. The investment required for the development of the economy, can not be fully effective if the formation of factors of production will not be taken into account the need for balance in all their elements: labor, capital, institutions, businesses, and others. Thus, the role of quality of labor and its productivity in terms of innovative development is increasing. Unfortunately, the scientific study of the socio-economic problems of labor has been forgotten. There is no developed standards for labor, and there is no conducted statistical reports in terms of productivity. It may be excessive labor intensity dictated by saving payroll. In this way, there is a need scientifically based state program for improving productivity.